2023
DOI: 10.3390/ijms24032470
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of a Wide Pisum spp. Core Collection

Abstract: Peas (Pisum sativum) are the fourth most cultivated pulses worldwide and a critical source of protein in animal feed and human food. Developing pea core collections improves our understanding of pea evolution and may ease the exploitation of their genetic diversity in breeding programs. We carefully selected a highly diverse pea core collection of 325 accessions and established their genetic diversity and population structure. DArTSeq genotyping provided 35,790 polymorphic DArTseq markers, of which 24,279 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 76 publications
2
10
0
Order By: Relevance
“…Plant material consisted in a diverse core collection of 320 Pisum accessions of worldwide origin gathered previously at Institute for Sustainable Agriculture – CSIC to ensure an extensive range of characteristics in terms of phenotype and their genetic makeup (Rispail et al 2023). The collection includes accessions that have already demonstrated their potential for resistance to several pea diseases including rust (accessions IFPI3260, PI347352, PI347343, PI347353 and PI347389) (Barilli et al 2009a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant material consisted in a diverse core collection of 320 Pisum accessions of worldwide origin gathered previously at Institute for Sustainable Agriculture – CSIC to ensure an extensive range of characteristics in terms of phenotype and their genetic makeup (Rispail et al 2023). The collection includes accessions that have already demonstrated their potential for resistance to several pea diseases including rust (accessions IFPI3260, PI347352, PI347343, PI347353 and PI347389) (Barilli et al 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…The process of DNA extraction, DArTseq protocol, and data analysis were previously detailed in Rispail et al (2023). In summary, the genotyping of the pea core collection was carried out using the DArTSeq approach, as described by Barilli et al (2018).…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown genetic diversity in Pisum germplasm (Annicchiarico, Romani, et al, 2017; Rispail et al, 2023; Smýkal et al, 2011; Yang et al, 2022). The primary gene pool for domesticated peas consists of P. sativum , its subsp.…”
Section: Pea Genetic Resources and Genomic Tools For Drought Adaptati...mentioning
confidence: 99%
“…The high diversity of key traits in wild and domesticated peas is promising for the strategic crossing of complementary genotypes. This variation is an essential source of desired alleles in the agronomic, physiological and biochemical traits to improve drought adaptation and yield gains in other pea crops (Rispail et al, 2023; Smýkal et al, 2018; Yang et al, 2022).…”
Section: Pea Genetic Resources and Genomic Tools For Drought Adaptati...mentioning
confidence: 99%